The Epistemic Integration Between Arabic Sciences and Islamic Jurisprudence: Grammar, Pausing, and Starting as a Model - Farag, Hady Hussein Abdalla (Journal of Ecohumanism, 2024)
This research addresses the epistemic integration between Arabic and Islamic sciences in general, with a specific focus on grammar, pausing, and starting. It highlights the primary aspects of this epistemic integration and clarifies them for the reader, while also showcasing the efforts of Arabic and grammar scholars in establishing and systematizing the science of pausing and starting. Additionally, it examines the impact of grammatical forms and syntax on pausing, starting, and Quranic recitation. This study follows the inductive-analytical method, as it relies on examining the connections between grammar and the science of pausing and starting, presenting and analyzing selected verses from the Quran where multiple grammatical forms exist, and discussing how these variations affect pausing and starting choices. The research reveals the close relationship between grammar and the science of pausing and starting, emphasizing that only those thoroughly knowledgeable in Arabic grammar can undertake this field. Furthermore, the study highlights the influence of grammar and syntactical forms in diversifying pausing and starting, establishing its rules, and the dedication of Arabic scholars to writing on the science of pausing and starting.